1993
DOI: 10.1111/j.1432-1033.1993.tb18084.x
|View full text |Cite
|
Sign up to set email alerts
|

Human α and β parvalbumins

Abstract: α and β parvalbumins are Ca2+‐binding proteins of the EF‐hand type. We determined the protein sequence of human brain α parvalbumin by mass spectrometry and cloned human β parvalbumin (or oncomodulin) from genomic DNA and preterm placental cDNA. β parvalbumin differs in 54 positions from α parvalbumin and lacks the C‐terminal amino acid 109. From MS analyses of α and β parvalbumins we conclude that parvalbumins generally lack posttranslational modifications. α and β parvalbumins were differently expressed in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 59 publications
0
49
0
Order By: Relevance
“…Two evolutionarily distinct lineages, the a-type PVs (109 amino acids) and the j3-PVs (108 amino acids) are present in several tissues including the brain of lower and higher vertebrates (31 slow exchange rate (75), to buffer the increase in calcium ions. Exceptionally, oncomodulin, a n-type PV which was first discovered in chemically induced rat hepatomas (55% identity with rat muscle PV) possesses one high affinity Cat+-Mg2+ mixed site and one characteristic low affinity Cat-specific site (22).…”
mentioning
confidence: 99%
“…Two evolutionarily distinct lineages, the a-type PVs (109 amino acids) and the j3-PVs (108 amino acids) are present in several tissues including the brain of lower and higher vertebrates (31 slow exchange rate (75), to buffer the increase in calcium ions. Exceptionally, oncomodulin, a n-type PV which was first discovered in chemically induced rat hepatomas (55% identity with rat muscle PV) possesses one high affinity Cat+-Mg2+ mixed site and one characteristic low affinity Cat-specific site (22).…”
mentioning
confidence: 99%
“…The function of the SA node and the AV node is the generation and conduction of electrical impulses, which are different from those in cardiomyocytes, whose primary function is contraction. Therefore, we suggest that the function of parvalbumin in the SA and AV nodes may be similar to that in neurons, where parvalbumin acts as an intracellular Ca 2+ -buffering transport protein [15][16][17][18] . It has been suggested that parvalbumin may influence the electrical properties and enzymatic machinery which modulate neuronal excitability and activity 9 .…”
Section: Scienceasia Scienceasia Scienceasiamentioning
confidence: 99%
“…Several PV isoforms exist, which have been placed in a subfamily of the superfamily of EF-hand Ca 2 ϩ binding proteins (Moncrief et al 1990;Nakayama et al 1992). Two different isoforms, ␣ and ␤, can be distinguished by their different biophysical characteristics (Föhr et al 1993). However, in adult human only a single ␣-PV form is expressed (Föhr et al 1993) whereas a ␤-PV is found exclusively extraembryonically in the placenta and in human tumors .…”
mentioning
confidence: 99%
“…Two different isoforms, ␣ and ␤, can be distinguished by their different biophysical characteristics (Föhr et al 1993). However, in adult human only a single ␣-PV form is expressed (Föhr et al 1993) whereas a ␤-PV is found exclusively extraembryonically in the placenta and in human tumors . PV has been localized in metabolically active cells such as fast-twitch muscle fibers, GABAergic neurons, and several endocrine glands (Berchtold 1989).…”
mentioning
confidence: 99%